(untitled) (Jurnal SPEKTRUM, 2025)
The adoption of new technology in professional settings is often hindered by low user acceptance, making usability a key factor in successful implementation. This study aims to assess the perceived usability of a web-based administrative information system for the Coass program at the Dental and Oral Hospital (RSGM). The evaluation used the System Usability Scale (SUS) method with 41 respondents, including Coass students, dentists, and administrative staff. The average SUS score was 80.121, categorized as "Excellent." These results indicate that the system is highly user-friendly and well-accepted, reflecting effective interface design and user experience as strong indicators of institutional adoption.